Modelagem geometalúrgica dos índices de cominuição em combinações de diferentes litologias presentes na mina de Chapada - Alderney Alexander Moreira (2023)
Geometallurgy focuses on the integration of the many areas of the mineral value chain. Modeling and predicting plant performance when fed with combinations of different lithologies is a major challenge for geometallurgy, since comminution indexes and metallurgical recovery are non-additive variables. The comminution stage is of fundamental importance in the operation of the Chapada mine, as it constitutes the bottleneck for increasing production at the unit. The variability of the ore fed in the circuit constitutes a constant challenge for the production planning, as it directly affects the performance of the grinding stage. In this work, the main comminution indexes were determined for binary compositions of different lithologies present in the mine. The results confirmed the non-additivity of the comminution indexes and models were developed in an attempt to predict the results of lithology mixtures in different proportions.